Risk Analysis Related to the Possibility of Using CNG in Trans Jogja Buses - Perwitasari, Perwitasari; Anggorowati, Heni; Yusuf, Yusmardhany (CHEESA: Chemical Engineering Research Articles, 2022)
One of the issues in urban areas such as DI Yogyakarta province is air pollution. The pollution level is high, as shown by the quality index value of about 85.25 in 2019. Vehicle emissions are the most significant source of this pollution in urban areas and can be decreased by using fuel with minimum carbon emission. Compressed Natural Gas (CNG) is an environmentally friendly fuel. However, a safety study is required because CNG is stored under high pressure. Therefore, this research aims to analyze the risk of using CNG in the Trans Jogja bus. The research method collects secondary data and then processes them using FTA, ETA, ALOHA software, and a risk matrix. The result shows that the risk value for CNG usage in the Trans Jogja bus is low to a moderate level or acceptable.